2013
DOI: 10.1021/ma301791n
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Histidine-Based Transient Network Metal Coordination Hydrogels

Abstract: Transient network hydrogels cross-linked through histidine-divalent cation coordination bonds were studied by conventional rheologic methods using histidine-modified star poly(ethylene glycol) (PEG) polymers. These materials were inspired by the mussel, which is thought to use histidine-metal coordination bonds to impart self-healing properties in the mussel byssal thread. Hydrogel viscoelastic mechanical properties were studied as a function of metal, pH, concentration, and ionic strength. The equilibrium met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
330
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(354 citation statements)
references
References 54 publications
20
330
2
2
Order By: Relevance
“…We notice that the catechol might not be the only group that has coordination ability in our polyoxetane-based adhesive, and the triazole group formed via CuAAC could also form networks by forming triazole-metal complex [26,27], which might also contributes to the enhancement of the cohesive strength and adhesive strength. Also, the triazole group is structurally similar to the imidazole moiety in histidine, another important amino acid moiety in mfps that has the coordination ability [28,29]. Thus we speculated that one possible reason for lower catechol content requirement to achieve excellent bonding strength in our case is the coordination ability of triazole groups towards Fe 3þ .…”
Section: Characterization Of the Adhesive Propertiesmentioning
confidence: 84%
“…We notice that the catechol might not be the only group that has coordination ability in our polyoxetane-based adhesive, and the triazole group formed via CuAAC could also form networks by forming triazole-metal complex [26,27], which might also contributes to the enhancement of the cohesive strength and adhesive strength. Also, the triazole group is structurally similar to the imidazole moiety in histidine, another important amino acid moiety in mfps that has the coordination ability [28,29]. Thus we speculated that one possible reason for lower catechol content requirement to achieve excellent bonding strength in our case is the coordination ability of triazole groups towards Fe 3þ .…”
Section: Characterization Of the Adhesive Propertiesmentioning
confidence: 84%
“…23 Additionally, a new generation of biomimetic self-repairing metallopolymers has arisen, which directly draw inspiration from the byssal threads. [24][25][26][27] In spite of these advances, many challenges still persist. Thus, a thorough experimental and theoretical understanding of the molecular processes underlying the SB mechanism is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown, for example, that the type of coordination bond (i.e. the metal and ligand utilized) affects the stiffness and strength of a polymer 25,27,28 and that the fracture toughness as well as the extensibility of materials based on SBs is strongly dependent on the pulling speed. 29,30 Furthermore, it was shown that the topology of SBs and thermal backbone fluctuations strongly affect the efficacy of SBs 31 and that the spatial distribution of SBs can have a strong effect on mechanics 32 -a random distribution of SBs is necessary to provide the system with shear deformability.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Cu 2+ /carboxyl, 13 Fe 3+ /catechol, 14,15 and Ni 2+ /histidine interactions were also employed. 16,17 Self-healing is a very interesting and useful feature of metal-coordinated gels; broken gel pieces can seal together with a mild mechanical force.…”
mentioning
confidence: 99%